Estratégias construtivas para a configuração do produto de moda - Souza, Patrícia de Mello [UNESP]; Menezes, Marizilda dos Santos [UNESP] (Universidade Estadual de Londrina, 2011)
This article approaches possibilities and strategies of building to development of fashion product. It investigates the application of different constructive resources of textile materials of same composition and trim, establishing for this parameters of formal similarity. The conception of products process is conducted by three-dimensional expression, which allows the steps for creating and delivering happen simultaneously. Three-dimensional modeling techniques enable the buildings that are structured by the following features investigated: intervention in the textile surface, insertion of independent elements, and different confection resolutions. The results instigate reflection about the processes involved.

O presente artigo trata das possibilidades e estratégias de construção para o desenvolvimento do produto de moda. Investiga-se a aplicação de diferentes recursos construtivos aos materiais têxteis de mesma composição e caimento, estabelecendo, para tanto, parâmetros de similaridade formal. O processo de concepção dos produtos é conduzido pela expressão tridimensional, o que permite que as etapas de criação e materialização aconteçam de modo simultâneo. Técnicas de modelagem tridimensional viabilizam as construções que são estruturadas pelos seguintes recursos investigados: intervenção na superfície têxtil, inserção de elementos independentes e diferentes resoluções de confecção. Os resultados obtidos instigam à reflexão acerca dos processos envolvidos.
Construction strategies for the fashion product configuration
Keywords: Fashion design; Modeling; Constructive resources; Design de moda; Modelagem; Recursos construtivos